Analisis Manajemen Inventori Consumable Goods Dotting Gloves dengan Metode Buffer Stock dan Reorder Point - Achmad Fikry; Sugiyanto, Sugiyanto; Aisyah, Nyayu; Prihadianto, Braam Delfian (Jurnal Teknologi dan Rekayasa Alat Berat, 2024)
This research aims to optimize consumable goods inventory control for dotting gloves items in a heavy equipment company. The inventory control process uses mathematical calculation methods, namely additional inventory (buffer stock) and reorder points as well as designing a web-based inventory application system. The research results showed that stock outs occurred repeatedly for dotting gloves. In 2023, the initial inventory of this item will be out of stock for 4 months. The frequency of purchasing dotting gloves is relatively small, only done twice in 5 months. After calculating the buffer stock and reorder point, the company is advised to place a reorder when the stock of dotting gloves reaches 83 pairs or 7 dozen to maintain the continuity of the company's operations. Next, a web-based inventory management application was created to automatically detect reorder points on dotting glove items.